The message : the extraordinary journey of an ordinary text message - Emberley, Michael (Atheneum Books for Young Readers, 2021)
"Ever wonder how your text message gets from your phone to your friend's phone? You type it, hit send, and boom -- the text appears on your friend's phone just moments later. But how?! From your brain to your fingers to your phone, once you hit send, off your message goes on a journey that seems impossibly far: traveling through the air, underground, under oceans, and even through mountains, in seconds. Turns out texts are big on adventure, and this book explains exactly what they do and how. No planes, trains, or automobiles involved, but lots and lots of hair-thin fibers, ocean-length cables, and satellites!"--